A Potential Objective Sign of Central Sensitization: Referred Pain Elicited by Manual Gluteus Minimus Muscle Exploration is Coincident with Pathological Autonomic Response Provoked by Noxious Stimulation - Elzbieta Skorupska; Tomasz Dybek; Michał Rychlik; Marta Jokiel; Paweł Dobrakowski; Anna Szczerba; Daria Wotzka; Anna Jankowska (Pain Research and Management)
Referred pain/sensation provoked by trigger points suits the nociplastic pain criteria. There is a debate over whether trigger points are related to a peripheral phenomenon or central sensitization (CS) processes. Referred pain is considered a possible sign of CS, which occurs probably mainly due to the abnormal activity of the immune and autonomic nervous systems. To confirm abnormal autonomic reactivity within the referred pain zone of active trigger points, a new diagnostic tool, the Skorupska Protocol® (the SP test®), was applied. The test uses noxious stimulation (10 minutes of dry needling under infrared camera control) as a diagnostic tool to confirm abnormal autonomic nervous system activity. A response to the SP test® of healthy subjects with referred pain sensations provoked by latent trigger points (LTrPs) stimulation was not explored before. The study aims at examining if LTrPs can develop an autonomic response. Methods. Two groups of healthy subjects, (i) gluteus minimus LTrPs with referred pain (n = 20) and (ii) control (n = 27), were examined using the SP test®. Results. Abnormal autonomic activity within the referred pain zone was confirmed for all analyzed LTrPs subjects. 70% of control subjects had no feature of vasodilatation and others presented minor vasomotor fluctuations. The size of vasomotor reactivity within the referred pain zone was LTrPs 11.1 + 10.96% vs. control 0.8 + 0.6% p<0.05. Conclusions. Noxious stimulation of latent TrPs induces abnormal autonomic nervous system activity within the referred pain zone. The observed phenomenon supports the concept of central nervous system involvement in the referred pain patomechanizm.